1996
DOI: 10.1111/j.1439-0442.1996.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinuclear Antibodies in Dogs with Leishmaniasis

Abstract: An indirect immunofluorescence method using rat liver as material was developed to determine the incidence of antinuclear antibodies in serum from 44 adult dogs naturally infected with leishmaniasis and, for comparative purposes, in a control group of 30 healthy dogs. Animals in both groups were of different breeds with a similar age distribution. Antinuclear antibodies were not detected in the healthy dogs and only 15.9 Yo of the diseased dogs, 12.0 YO males and 21.1 Yo females, were positive. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…A study from Spain reported ANAs in 15.9% of dogs with disease manifestations that were attributed to leishmaniasis. 4 That study found no cause-and-effect relationship between the presence of ANAs and renal failure in dogs with leishmaniasis. Two subsequent studies from Spain and Italy found the incidence of ANAs in dogs naturally infected with L infantum to be 10 and 47%, respectively.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A study from Spain reported ANAs in 15.9% of dogs with disease manifestations that were attributed to leishmaniasis. 4 That study found no cause-and-effect relationship between the presence of ANAs and renal failure in dogs with leishmaniasis. Two subsequent studies from Spain and Italy found the incidence of ANAs in dogs naturally infected with L infantum to be 10 and 47%, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous reports have identified ANAs in dogs with chronic bacterial and protozoal infections, particularly leishmaniasis. [3][4][5][6][7][8][9] Some evidence also exists to support the theory that transmissible agents may induce ANAs in dogs as well as in people. In one study, an increased occurrence of ANAs was detected in sera from clinically normal dogs owned by humans concurrently diagnosed with SLE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary renal disease. Underlying disorders causing secondary renal disease and subsequent increases in P‐creatinine include babesiosis, 166,188,189 leishmaniasis, 190–194 leptospirosis, 195–198 borreliosis, 199–200 trypanosomiasis, 201,202 heartworm disease, 203 encephalitozoonosis, 204 malignant histiocytosis, 205 pyometra, 206–209 experimental intestinal obstruction, 210 gastric dilatation/torsion, 211 diabetes mellitus, 212,213 and hypercalcemia caused by hyperparathyroidism 214 or lymphoma 215 . The magnitude of increase in P‐creatinine differed greatly according to the severity of the underlying disorder.…”
mentioning
confidence: 99%
“…The production of circulating immune complexes (Lopez et al, 1996) and autoantibodies such as antinuclear antibodies (anti-DNA, RNA, nuclear proteins and their molecular complexes), and anti-mammalian basal membrane glycoproteins and cerebrosides, and anti-Histone, was previously described in L. infantum-infected dog's sera (Pateraki et al, 1983;Lucena and Ginel, 1998;Bell et al, 1997;Smith et al, 2004). Ferrer (1992) and Lucena et al (1996) reported a 30 and 15.9% incidence of antinuclear antibodies in dogs with natural Leishmania infection, respectively. Pateraki et al (1983) demonstrated by ELISA that 250 (95%) and 248 (94%) dogs out of 260 with cVL, all positive for L. donovani antigens, have anti-actin and anti-tubulin IgG autoantibodies, respectively.…”
Section: A C C E P T E Dmentioning
confidence: 95%